2022
DOI: 10.1093/ehjqcco/qcac072
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality-of-life up to one year after myocardial infarction with non-obstructive coronary arteries

Abstract: Aims Patients with Myocardial Infarction with Non-Obstructive Coronary Arteries (MINOCA) is a heterogenous group and previous studies indicate a decreased Health-Related Quality-of-Life (HRQoL) compared to patients with myocardial infarction with obstructive coronary artery disease and healthy individuals. However, longitudinal data are scarce. Therefore, the aim was to explore HRQoL among patients with MINOCA during a one-year period after the acute event in comparison to a group of healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…This may be explained by the lack of a consensus strategy for treatment of MINOCA due to the lack of prospectively designed randomised therapeutic clinical trials; hence, guidelines are based on observational studies and expert opinion [13]. Nevertheless, it is concerning that these MINOCA patients are undertreated, as there have been studies showing the impact on their health status [18]. In a study by Grozinsky et al [19], it was revealed that 25% of MINOCA patients have ongoing chest pain and a reduced quality of life at 12-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by the lack of a consensus strategy for treatment of MINOCA due to the lack of prospectively designed randomised therapeutic clinical trials; hence, guidelines are based on observational studies and expert opinion [13]. Nevertheless, it is concerning that these MINOCA patients are undertreated, as there have been studies showing the impact on their health status [18]. In a study by Grozinsky et al [19], it was revealed that 25% of MINOCA patients have ongoing chest pain and a reduced quality of life at 12-month follow-up.…”
Section: Discussionmentioning
confidence: 99%